Cellular senescence: at the nexus between ageing and diabetes - Palmer, Allyson K. (Diabetologia, 2019)
Ageing and diabetes lead to similar organ dysfunction that is driven by parallel molecular mechanisms, one of which is cellular senescence. The abundance of senescent cells in various tissues increases with age, obesity and diabetes. Senescent cells have been directly implicated in the generation of insulin resistance. Recently, drugs that preferentially target senescent cells, known as senolytics, have been described and recently entered clinical trials. In this review, we explore the biological links between ageing and diabetes, specifically focusing on cellular senescence. We summarise the current data on cellular senescence in key target tissues associated with the development and clinical phenotypes of type 2 diabetes and discuss the therapeutic potential of targeting cellular senescence in diabetes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-019-4934-x) contains a slideset of the figures for download, which is available to authorised users.